2003
DOI: 10.1007/s00213-002-1307-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoxetine and d-fenfluramine on cocaine-seeking behavior in rats

Abstract: These findings suggest that 5-HT indirect agonists effectively attenuate cocaine-seeking behavior elicited by cocaine-associated stimuli, but are much less effective in attenuating cocaine-seeking behavior elicited by cocaine priming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 42 publications
6
53
0
Order By: Relevance
“…Consistent with our previous research (Burmeister et al, 2003), d-fenfluramine attenuated cue reinstatement, and this effect was reversed by SB 242,084. Previous research has shown that SB 242,084 does not alter basal locomotor activity (Fletcher et al, 2002b), but does potentiate d-fenfluramine-induced hyperactivity (Higgins et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our previous research (Burmeister et al, 2003), d-fenfluramine attenuated cue reinstatement, and this effect was reversed by SB 242,084. Previous research has shown that SB 242,084 does not alter basal locomotor activity (Fletcher et al, 2002b), but does potentiate d-fenfluramine-induced hyperactivity (Higgins et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The present study also examined whether the respective antagonists could reverse the d-fenfluramine-induced attenuation of cue-elicited reinstatement that we reported previously (Burmeister et al, 2003).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Treatment with dexfenfluramine reduces responding for a CRf (Fletcher, 1995;Wilson et al, 2000), while whole-brain 5-HT neuron ablation enhances this behavior (Fletcher et al, 1999). In tests of drug-seeking behavior, dexfenfluramine and the SSRI fluoxetine also diminished the ability of a cocaine-paired stimulus to reinstate responding under extinction conditions (Baker et al, 2001;Burmeister et al, 2003). Furthermore, we have recently shown that another SSRI, citalopram, reduced responding for a CRf and a USRf (Browne et al, 2016).…”
Section: Introductionmentioning
confidence: 93%